(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The essay analyzes some recent decisions of the Italian Court of Cassation in the field of the Medical Assisted Reproduction, in order to explore the evolution of the “international public order” clause from a constitutional perspective; most notably with regard to the different role played both by the Courts and the Parliament in addressing the issue of the legal effects of the “procreative tourism” in the Italian legal system).